Oracle PL/SQL best practices - Feuerstein, Steven; Safari eBooks (Sebastopol, Calif. : O'Reilly Media, Inc., 2007)
"This book summarizes PL/SQL best practices in nine major categories: overall PL/SQL application development; programming standards; program testing, tracing, and debugging; variables and data structures; control logic; error handling; the sue of SQL in PL/SQL; building procedures, functions, packages, triggers; and overall program performance"--Cover.
"Write the best PL/SQL code of your life"--Cover.
"Covers Oracle database 11g"--Cover.
Includes bibliographical references (p. 252-258) and index.
Electronic reproduction.
Keywords: Oracle (Computer file); PL/SQL (Computer program language); Relational databases; Electronic books